Labor-market performance in the OECD: an assessment of recent evidence - Sergio Destefanis; Giuseppe Mastromatteo (Levy Economics Institute of Bard College, 2009)
In this paper we assess the evolution of labor-market performance in the Organisation for Economic Co-operation and Development (OECD) over the last decade. We provide a survey of the literature dealing with labor-market performance in the OECD, finding that, while this literature tends to conclude that institutions are a key part of the story, the survey's results appear far less robust and uniform than is commonly believed. We then assess the robustness of the claims made in the most recent (2005) OECD followup study within a very similar cross-country setup, and highlight the impact of unobserved heterogeneity and outliers on the policy estimates. We find that in recent OECD cross-country data, changes in labor-market performance are consistently (and inversely) linked to its lagged level. Structural changes are also important: changes in the share of construction employees are very significant, even in the presence of various kinds of policy change indicators. As far as the latter are concerned, some consistent role seems to emerge only for active labor-market policies and (to a lesser extent) unemployment benefit reforms.
Keywords: E60; J60; 330; Cross-country labor-market comparisons; labor-market institutions; product-market institutions